Three novel species in the Pseudo‐nitzschia pseudodelicatissima complex: P. batesiana sp. nov., P. lundholmiae sp. nov., and P. fukuyoi sp. nov. (Bacillariophyceae) from the Strait of Malacca, Malaysia. Issue 5 (27th August 2013) - Lim, Hong Chang; Teng, Sing Tung; Leaw, Chui Pin; Lim, Po Teen; De, O.
<x xml:space="preserve">Abstract</x> A study on the morphology and phylogeny of 18 strains of Pseudo‐nitzschia established from the Strait of Malacca, Peninsular Malaysia, was undertaken. Morphological data combined with molecular evidence show that they constitute three new species, for which the names, P. batesiana sp. nov., P. lundholmiae sp. nov., and P. fukuyoi sp. nov., are proposed. The three new species closely resemble species in the P. pseudodelicatissima complex sensu lato. Morphologically, P. batesiana differs from other species in the complex by having a smaller part of cell overlapping in the chain, whereas P. lundholmiae differs by having fewer poroid sectors and P. fukuyoi by having a distinct type of poroid sectors. Nucleotide sequences of the LSU rDNA (D1–D3) of the three new species reveal significant nucleotide sequence divergence (0.1%–9.3%) from each other and from other species in the P. pseudodelicatissima complex s.l. The three species are phylogenetically closely related to species in the P. pseudodelicatissima complex, with P. batesiana appearing as a sister taxon to P. circumpora, P. caciantha, and P. subpacifica; whereas P. lundholmiae and P. fukuyoi are more closely related to P. pseudodelicatissima and P. cuspidata. The three species show 2–3 compensatory base changes (CBCs) in their ITS2 transcripts when compared to the closely related species. The ITS2 with its structural information has proven its robustness in constructing a better resolved phylogenetic framework for Pseudo‐nitzschia.